2010
DOI: 10.1002/bies.201000083
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial manoeuvres: Latest insights and hypotheses on mitochondrial partitioning during mitosis in Saccharomyces cerevisiae

Abstract: Movement and positional control of mitochondria and other organelles are coordinated with cell cycle progression in the budding yeast, Saccharomyces cerevisiae. Recent studies have revealed a checkpoint that inhibits cytokinesis when there are severe defects in mitochondrial inheritance. An established checkpoint signaling pathway, the mitotic exit network (MEN), participates in this process. Here, we describe mitochondrial motility during inheritance in budding yeast, emerging evidence for mitochondrial quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…Aside from their best-known role as producers of ATP, mitochondria regulate lipid and amino acid metabolism, redox regulation, calcium buffering, the production of heme, and apoptosis [33]. Given the fundamental and diverse nature of mitochondrial housekeeping functions, it is no surprise that their disruption is associated with numerous human diseases [3] and that checkpoints have been found in yeast that prevent division if problems in mitochondrial partitioning have occurred [34]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from their best-known role as producers of ATP, mitochondria regulate lipid and amino acid metabolism, redox regulation, calcium buffering, the production of heme, and apoptosis [33]. Given the fundamental and diverse nature of mitochondrial housekeeping functions, it is no surprise that their disruption is associated with numerous human diseases [3] and that checkpoints have been found in yeast that prevent division if problems in mitochondrial partitioning have occurred [34]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, in budding yeast, actin cables are employed to transport mitochondria from the mother cell to the bud cell [34], whereas in fission yeast, microtubules move the organelles to opposite poles [35]. The mechanisms in mammalian cells, however, remain poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Early work on scorpion spermatogenesis showed that mitochondria associate with microtubules at the mitotic spindle poles and are separated actively along with the chromosomes [16]. In fission yeast, mitochondria are delivered by microtubules to opposite cell poles during division to ensure faithful inheritance [17] and mitochondria in budding yeast are transported from mother to bud along actin cables [18], [19]. In the asymmetric division of Acricotopus germ line cells, mitochondria are preferentially segregated to one cell pole and may be involved in cell-fate determination [20].…”
Section: Introductionmentioning
confidence: 99%
“…a Data from yeast suggest that both ER and mitochondria are selectively segregated into the mother cell or bud (Du et al 2004; Lowe and Barr 2007; Peraza-Reyes et al 2010). b A mammalian cell showing the sequestration of an aggresome into one of the two daughter cells following cell division.…”
Section: Figmentioning
confidence: 99%
“…Thus, it is as if these mitochondria are tasked with walking up a down-escalator. Based on this, a model has been proposed whereby only the strongest, most functional mitochondria are able to overcome this opposition and are transported into the developing daughter cell (Peraza-Reyes et al 2010). …”
Section: Introductionmentioning
confidence: 99%